Determinants of Net Capital Expenditure Cash Outflows: Evidence from the Pharmaceutical Sector of Bangladesh - Abedin, Md. Thasinul; Sen, Kanon Kumar; Akter, Mahmuda (Asian Journal of Accounting Perspectives, 2017)
This study attempts to identify the key determinants of net capital expenditure outflows for a panel of 14 listed pharmaceutical companies. The study has used data from 2003-2015 for each company. The study finds that previous year net capital expenditure outflows, the age of the company, size of the company, leverage of the company, business risk of the company, and independent directors on the board of directors’ panel are the key determinants of net capital expenditure outflows. The study uses Panel GMM approach along with Fixed Effect OLS and PCSE OLS. Age of the company, size of the company, and percentage of independent directors have a significant positive impact on net capital expenditure outflows unlike business risk and leverage of the company. Keywords: Pharmaceutical Sector, Net Capital Expenditure Outflows, Business Risk JEL Classification: C33, E22, L65